Expression and regulation of N-Myc Downstream- Regulated gene 1 in squamous cell carcinoma of the oesphagus - Bracher, Jacqueline Claire (Division of Medical Biochemistry, 2014)
Squamous cell carcinoma of the oesophagus is a formidable disease which poses a significant health risk in developing countries where the incidence is frequently high and access to health care facilities is often limited. The identification of genes involved in oesophageal tumourigenesis may provide new targets for therapy and improved diagnostics techniques, thereby improving the prognosis of this pernicious disease. In this study, real-time RT-PCR and immunohistochemistry described the overexpression of N-Myc Downstream-Regulated Gene 1 (NDRG1) in oesophageal squamous cell carcinoma (OSCC) tissue compared to normal tissue in a cohort of South African cancer patients. Despite more than ten years of research into the role of NDRG1 in cancer, the precise function of this protein remains enigmatic. Reports have been contentious, suggesting both tumour suppressor and tumour promoter functions for NDRG1, implicating it in tumourigenic processes such as metastasis and angiogenesis. Our immunohistochemical analysis if NDRG1 expression in OSCC tissue and matched normal epithelium (n=83) showed that NDRG1 expression is elevated by 2.6-fold in cancer tissue compared to normal tissue. Moreover, the expression and localisation of NDRG1 appeared to track with epithelial cell maturation where basal cells of normal oesophageal epithelium displayed plasma membrane-associated NDRG1 while maturing cells were mostly positive for NDRG1 in the cytoplasm and nucleus. Likewise, NDRG1 displayed interesting patterns of localisation in tumour tissue of the xiii oesophagus. Dysplastic tissue and poorly differentiated tumour tissue stained positively for NDRG1 in the plasma membrane, while moderately and well differentiated tumours displayed mixed staining for NDRG1 in the plasma membrane, cytoplasm and nucleus. Analysis of NDRG1 expression in cell lines cultured under anchorage-independent conditions revealed that NDRG1 expression is strongly induced when cells are prevented from adhering to the surface of culture dishes. Induced NDRG1 expression correlated inversely with mRNA expression of invasion genes, MMP-2 and MMP-9, as well as the mRNA expression of angiogenic factors Ang- 1, PDGF-B and VEGF-C but, in contrast, showed positive correlation with the angiogenesis cytokine, VEGF-A. Knock-down of NDRG1 expression with siRNA had no effect on anchorage-independent cell proliferation or apoptosis but did inhibit VEGF-A expression. Moreover, VEGF-A promoter activity, induced by culturing cells under anchorage-independent conditions was shown to be NDRG1-dependent. In order to identify factors that may drive NDRG1 transcription in cultured OSCC cell lines we cloned and partly characterised the NDRG1 promoter. Through the generation of promoter deletion constructs, site-directed mutagenesis and Chromatin Immunoprecipitation (ChIP) assays, we showed that both EGR-1 and cJun/AP-1 are capable of driving transcription of NDRG1 in response to 12-o-tetradecanoylphorbol- 13-acetate (TPA) through activation of PKC/MEK/ERK1/2 and JNK MAPK pathways. Taken together, we describe the regulation of NDRG1 expression by EGR-1 and AP-1 and we show that NDRG1 is overexpressed in squamous cell carcinoma of the oesophagus compared to normal oesophageal tissue. We associate NDRG1 with an xiv oncogenic function in OSCC through its potential role in angiogenesis via modulation of VEGF-A expression.